К столетию двух великих взаимосвязанных патофизиологических открытий - Чурилов, Л.П.; Строев, Ю.И. (Таврический медико-биологический вестник, 2012)
Наводяться історичні відомості про розвиток вчення про атеросклероз, метаболічний синдром та аутоімунний тіроідіт, про їх взаємозв’язках. На підставі власних і літературних даних розглядається роль аутоімунного тіроідіта Хасімото як фактора, який приводить до розвитку метаболічного синдрому. У обстежених пацієнтів з тіроідітом Хасімото виявлені прояви метаболічного синдрому і зв’язок з контрактурою Дюпюітрена. Ступінь порушень була більш виражена при більшій окружності талії. The historical data on the research of atherosclerosis, metabolic syndrome and autoimmune thyroiditis are given, as well as their interrelationships. The article deals with original and literature data concerning the role of Hashimoto thyroiditis as a factor predisposing to development of metabolic syndrome. In a group of Hashimoto thyroiditis patients the elements of metabolic syndrome were revealed as well as connection to Dupuytren’s contracture. The severity of changes was greater in greater waist circumference.